2020
DOI: 10.1016/j.jpubeco.2020.104254
|View full text |Cite
|
Sign up to set email alerts
|

Polarization and public health: Partisan differences in social distancing during the coronavirus pandemic

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
700
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 821 publications
(840 citation statements)
references
References 42 publications
71
700
1
8
Order By: Relevance
“…However, the rise of anti-vaccination misinformation (e.g. misleading healthcare information, conspiracy theories) may also have played a role in explaining this increase [11][12][13][14]26 . It will therefore be critical that accurate safety information is widely and transparently communicated by trusted sources to promote confidence in the scientific decision-making underpinning the approval of COVID-19 vaccines 16,21 .…”
Section: Pg 12mentioning
confidence: 99%
“…However, the rise of anti-vaccination misinformation (e.g. misleading healthcare information, conspiracy theories) may also have played a role in explaining this increase [11][12][13][14]26 . It will therefore be critical that accurate safety information is widely and transparently communicated by trusted sources to promote confidence in the scientific decision-making underpinning the approval of COVID-19 vaccines 16,21 .…”
Section: Pg 12mentioning
confidence: 99%
“…As the pandemic varied markedly in its course across geographic regions, those who reside in states where the COVID-19 outbreak is more widespread and where there are more cases, may be more likely to take actions to maintain their health. Those who trust the current government and media that portrays the COVID-19 crisis with skepticism and downplays the danger of the virus are less likely to take preventive behaviors and more likely to take risky behaviors compared to those who trust media sources that portray the pandemic as risky and endorse public health recommendations [20][21][22][23][24]. Those who perceive a higher personal probability of getting the infection and dying are more likely to respond to behavioral modifications than those whose assessment of their risk for infection and death is low.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that the spreading prevalence of this new coronavirus is due to the mobility and interaction of people who have been transferred from one location to another through outbound flight, public transport, and joining crowds (McCloskey et al, 2020;Pluchino et al, 2020). Researchers and health experts are stressing on applying social alienation strategies, for instance, the workplace and cafe closures, exclusions of large public gatherings and religious pilgrimage, home quarantine or segregation, and traditional outbreak response technique-isolation, curfew, lockdown, social distancing, and community containment to curb the epidemic (Allcott et al, 2020;Wilder-Smith & Freedman, 2020). Subsequently, WHO, health professionals, and academia are also repetitively urging the world to maintain a social distance of 1 meter away from crowds and public gathering all over the globe (Abel & McQueen, 2020;Kumar, 2020; WHO, 2020) as a pro-active safety behavior to fight against COVID-19.…”
Section: Introductionmentioning
confidence: 99%